Apolipoprotein D, apolipoprotein R and ST6GalNAc4 genes respond to clenbuterol administration in pig adipose tissue - Jin Zhang; Jiali Lin, Liangcai Shen; Fan Zhang, Yingbo Zhu; Libin Zheng (African Journal of Pig Farming, 2018)
Pig fat accumulation can be reduced by feeding pigs with high dosages of clenbuterol, but the molecular mechanism has not yet been well characterized. cDNA microarray and real-time PCR were used to identify the molecules potentially responding to clenbuterol in adipose cells. The mRNAs of 17 genes were found to be differentially expressed more than 2 fold (ratios of the expression levels in the test pigs to those in the control pigs of more than 2 or less than 0.5) by microarray analysis, including three lipid metabolism related genes (apolipoprotein D, apolipoprotein R and ST6GalNAc4). Eight genes were verified by real-time PCR, with six of them reproducing the result from microarray analyses. The results showed that apolipoprotein D, apolipoprotein R and ST6GalNAc4 genes respond to clenbuterol administration in pig adipose tissue and their functions may relate to fat accumulation reduction.